Review of the 1977 Decision on Surveillance Over Exchange Rate Policies : Preliminary Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This review of the Decision forms part of a more comprehensive approach to strengthen the effectiveness of surveillance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet